Penerapan Metode K-Means Dalam Pengelompokkan Buku Untuk Menentukan Minat Baca Pada Perpustakaan Daerah Kota Medan - Harefa, Misael Oktavianda; Aripin, Soeb (Bulletin of Artificial Intelligence, 2024)
The library is a facility that functions as an information center, a source of various knowledge, research, recreation and cultural preservation. The Medan City Regional Library is a library organized by the regional government using general funds which aims to serve the public in obtaining comprehensive information without distinguishing gender, religion, race, age, occupation and position. In 2021 the Medan city regional library has 28 thousands of titles books in several categories. Of the many books contained in the library, a system must be needed where the system is useful for both the library and the reader in maximizing grouping of books and searching books easily by the reader, therefore the K-Means Clustering method is used, where the method This is a method in data mining that processes clustering data that is grouped into one or more clusters. In this study, 100 samples of book category data were used in the Medan City library. This study groups the data categories into 3 clusters, namely the most desirable, desirable and least desirable. The results of this method process will find out the most popular book category data so that in the future it will be a consideration for the librarian to increase the collection of books at the Medan City regional library. The process of calculating the K-Means method in grouping books is only carried out until the 2nd iteration because iteration -3 gets the same value. In Cluster 1 (Most Interested) choose 6 categories of books including Category 020-Library and Information, 070-Mass Media, Journalism and Publication, 050-Psychology, 420-Indonesian, 600-Technology, 650-Management. In Cluster 2 (Desired) choose 16 categories of books including 000-General Publications and General Information, 030-Encyclopedias and Books, 040-Biography, 050-Magazines and Journals, 090-Manuscripts and Rare Books, 210-Islamic Religion, 300-Science Social, 320-Political Science, 330-Economics, 410-Indonesian, 510-Mathematics, 620-Technical Sciences, 770-Photography and Photos, 780-Music, 910-General Travel Geography, 930-Old World History. And in cluster 3 (Less Interested) 78 categories of books were selected. 10 of them 010-Bibliography, 060-Association of Organizations and Museums, 080-Quotes, 100-Philosophy and Psychology, 110-Mathematics, 120-Epistimology, 030-Parapsychology and Occultism, 040-Philosophical Thought, 060 Logical Philosophy, 070-Ethics.